Evaluasi Pengendalian Internal di PT Pertamina Marketing Operation Region V - , ARIEF IRIANSYAH, Tauikur Rahman, S.E.,M.B.A ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research background is the increasing needs of fuel oil which is requiring PT Pertamina to undertake their operation distribution of BBM better. In order to increase the effectiveness and efficiency of the company's performance, it is required a good internal control. The aim of this research is to evaluate the effectiveness of the internal control in reaching the company's vision and mission, and also to get empirical prove in applying the elements of internal control in a company. This research is a qualitative research and uses observation, interview and questionnaire methods to get the data. The foundation of the research uses the components of COSO internal control. The data analysis is done by evaluating the empirical prove which is acquired from the result of the observation in the operation process, documents inspection, and employees' confirmation. As for the final result of this research, the company has already had a good internal control which has been run effectively. However, the internal control system can only push the possibility in the occurrence of any violation and cannot completely omit the violation itself. Therefore, an internal control should be designed dynamically, in accordance to the characteristic of the company.